MAINTENANCE STRATEGY IN PAVEMENT PERFORMANCE EVALUATIONS USING DEFLECTION MODEL AND SITE RECONNAISSANCE METHODS (Nigerian Journal of Technology, 2018)
This paper presents the results of a comparative study of a pavement evaluation for maintenance strategy option using deflection model and condition survey methods. Condition survey was carried out to visually assess the distress manifestations on the study section of the road. Test samples were collected at various locations within the road section, after which some engineering properties - natural moisture content, in-situ dry density, optimum moisture content, maximum dry density, and relative density, were determined for them. The pavement deflections at these locations were calculated using a deflection model. The representative rebound deflection, ?rrd, was thereafter determined. A pavement rating score (PRS) of 61% was obtained from the condition survey, which suggests that the pavement is in good condition and thus requires overlay only. A representative deflection value of 0.4 mm obtained also suggests that the pavement is in good condition. These results show that the two methods corroborate each other and should be used together to evaluate road sections for the optimum road maintenance option. http://dx.doi.org/10.4314/njt.v37i4.1